2021
DOI: 10.13189/app.2021.090405
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Activity of Nigella sativa against Caenorhabditis elegans

Abstract: Increasing resistance against classical anthelmintic drugs makes discovering new anthelmintic compounds from natural plants important. Nigella sativa (N. sativa) is used as a medicinal plant overall the world and is known to have anthelmintic activity. Caenorhabditis elegans (C. elegans), a common cost-effective model organism that is easily maintained, is useful to determine the anthelmintic activity of new compounds derived from natural products. In our study we aimed to evaluate through toxicity assays the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Thymoquinone is also reported to cause oxidative damage to worm proteins and to increase host immunity as a defense against parasites (Ullah et al, 2017;Angel et al, 2018). Sen et al (2021) reported that thymoquinone could inhibits nonenzymatic lipid peroxidation, thus it will affect the organism's lipid structures. Another study by El-Naggar et al (2010) reported that black cumin had a sedative effect and the ability to accelerate the release of gamma-amino butyric acid (GABA).…”
Section: Resultsmentioning
confidence: 99%
“…Thymoquinone is also reported to cause oxidative damage to worm proteins and to increase host immunity as a defense against parasites (Ullah et al, 2017;Angel et al, 2018). Sen et al (2021) reported that thymoquinone could inhibits nonenzymatic lipid peroxidation, thus it will affect the organism's lipid structures. Another study by El-Naggar et al (2010) reported that black cumin had a sedative effect and the ability to accelerate the release of gamma-amino butyric acid (GABA).…”
Section: Resultsmentioning
confidence: 99%
“…Al-Shaibani et al [ 60 ] found that aqueous and ethanol extracts of N. sativa had ED 50 values on in vitro egg hatching of a mixture of GI sheep nematodes, including H. contortus , of 2.2 × 10 7 ng/mL and 2 × 10 7 ng/mL, respectively, and both extracts reduced in vivo egg counts by 200 mg/kg p.o compared to untreated control sheep. In another study, the essential oil of N. sativa at 9 × 10 8 ng/mL significantly reduced the survival of C. elegans larval and adult stages compared to negative (1% ethanol) and positive (levamisole at 8 × 10 6 ng/mL) controls, with larvae being more sensitive than adult worms [ 61 ]. The seeds of N. sativa contain fixed and volatile oils, rich sources of quinones, unsaturated fatty acids, amino acids and proteins, and traces of alkaloids and terpenoids.…”
Section: Discussionmentioning
confidence: 99%